(untitled) (Existential Analysis: Journal of the Society for Existential Analysis, 2007)
This paper looks at the Kierkegaardian leap of faith and considers whether it is possible for an existential therapist to make such a leap. It is argued that for Kierkegaard the ’how’ of faith – a passionate commitment to one’s own subjective truth – is inextricably linked with the ’what’ of faith – namely a leap into the arms of a creator God. Consequently, it is problematic to take Kierkegaard’s leap of faith as a general inspiration to follow one’s own internal conviction. It is also argued that Kierkegaard’s leap of faith possibly represents an attempt to step outside of relationship with others and, as such, is not necessarily an option for an existential therapist whose subjective truth is always in the process of being co-created in relationship.